Buckypaper of polyvinyl chloride/p-phenylenediamine modified graphite and PVC/graphite via resin infiltration technique - Khan, Zaheen Ullah; Kausar, Ayesha; Zhang, Dengsong; Shi, Liyi; Ullah, Hidayat; Khan, Wasid Ullah [UNESP] (Wiley-Blackwell, 2018)
Resin-infiltration technique has been employed as a versatile method to improve nanofiller dispersion in matrix. In this article, fabrication of polyvinyl chloride (PVC)/p-phenylenediamine (PPD)/functional graphite (F-G) and PVC/F-G composite paper have been reported through resin-infiltration techniques. Synthesis and characterization of PVC/PPD/F-G and PVC/F-G composite papers for enhanced structural, morphological, thermal, hardness, wettability, and conductivity properties have been studied. Moreover, the effect of increasing amount of F-G and PPD/F-G nanofiller on composite paper properties was scrutinized and compared. Transmission electron microscopy and scanning electron microscopy depicted better graphite nanofiller dispersion in PVC matrix and network formation in PVC/PPD/F-G composite paper. Maximum degradation temperature (T-max) of PVC/PPD/F-G 0.08 composite paper (517 degrees C) was found higher than PVC/F-G 0.08 composite paper (484 degrees C). Dynamic contact angle analysis shows that the PVC/PPD/F-G and PVC/F-G composite papers have better surface wettability than neat PVC. PVC/PDD/F-G 0.1 and PVC/F-G 0.1 composite papers possess high microhardness values up to 39.67 and 32.76Hv, respectively. Electrical conductivity of 8.97 x 10(-3) and 5.89 x 10(-3) Sm-1 was observed for 0.08 wt% PPD/F-G and F-G loaded samples. POLYM. COMPOS., 39:4176-4187, 2018. (c) 2017 Society of Plastics Engineers